2020
DOI: 10.1038/s41405-020-0043-7
|View full text |Cite
|
Sign up to set email alerts
|

A critical synthesis of the role of the pharmacist in oral healthcare and management of medication-related osteonecrosis of the jaw

Abstract: To consolidate extant published evidence in relation to the potential of integrating oral healthcare for patients at risk of developing medication-related osteonecrosis of the jaw (MRONJ). METHODS: A critical synthesis and consolidation of five publications was undertaken. As a mechanism of situating the extant work within the context of primary healthcare provision, the Rainbow Model of Integrated Care was applied as a theoretical lens through which the conceptual findings could be collectively applied to pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…However, our study found limited communication and referral pathways between dental, medical and pharmacy services, alongside participants reporting significant challenges in getting patients to access and engage with dentists. This is further supported by existing literature that highlights the lack of integration of dental teams within other NHS services 21 22…”
Section: Discussionmentioning
confidence: 53%
“…However, our study found limited communication and referral pathways between dental, medical and pharmacy services, alongside participants reporting significant challenges in getting patients to access and engage with dentists. This is further supported by existing literature that highlights the lack of integration of dental teams within other NHS services 21 22…”
Section: Discussionmentioning
confidence: 53%
“…One study by Sturrock et al, exploring dental professionals' attitudes towards MRONJ and current multidisciplinary team approaches to care, showed that dental professionals felt there was little collaboration between themselves and pharmacists and general communication was around prescribing errors and drug interactions. 14 The study also showed dental professionals were willing to engage with other healthcare professionals to improve patient care. In particular, better communication with pharmacists was considered to be beneficial to dental professionals.…”
Section: Discussionmentioning
confidence: 89%
“…[ 8 ] In developing countries like Nigeria, individuals with ill health, especially dental diseases, first consult the pharmacist to seek dental advice and procure drugs from them before visiting the dental clinic. [ 19 ] More corroboration between dentists and pharmacists to improve the oral health knowledge of pharmacists is recommended. The pharmacy undergraduate curriculum can be modified to accommodate some dental topics in the course of training.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 , 16 ] Some of the barriers to the production of leaflets, pamphlets, and posters on oral health, in addition to seminars and oral health care training[ 16-18 ] are some of the preferred choices for improving oral health knowledge among pharmacists. An interdisciplinary approach that includes pharmacists in the management of dental conditions[ 19 ] has also been suggested.…”
Section: Introductionmentioning
confidence: 99%